O Serviço de Terapêutica Ocupacional e Reabilitação no PNP do H.C.E. - Ramos Vianna, Tong; Ferreira Duarte Filho, Antônio; Lerner, Luiz; Galvão de França, Dirceu; Duarte do Nascimento, Inalda (Revista Brasileira de Saúde Militar, 2022)
Resumo